Estudio de la calidad del agua potable en barrios del sector de la curva de la parroquia puerto bolivar, 2021 - Pineda Encalada, Viviana Solange (Machala : Universidad Técnica de Machala, 2022)
The increase in pollutants of natural or anthropogenic origin has generated a deterioration in the quality of groundwater, transforming this water resource into a source not suitable for human consumption. The protection and correct collection of water allows in this way to guarantee the quality of the source of supply for the drinking water service. This work aims to determine the water quality of the neighborhoods of the sector of the curve of the Puerto Bolívar parish that distributes the purification plant of the Gonzales Rubio well through the analysis of the physical-chemical and microbiological parameters, to evaluate them under national and international regulations. The samples were taken in each neighborhood at the stopcock of the water distribution network of the treatment plant within a prudential period of 15 days; November 7, 22 and December 7, 2021 where in situ physicochemical indicators such as pH, total dissolved solids, electrical conductivity, and temperature were determined by means of a multiparametric analyzer, the analysis of color, dissolved oxygen, residual chlorine and fecal coliforms were carried out in the laboratories of the UTMACH, with the exception of arsenic that was at the National Polytechnic University of Quito. The results obtained were compared with the permissible limits of the INEN Technical Standard 1108:2020-04. It was shown that most of the samples taken meet the physicochemical indicators except for 5 neighborhoods such as Harry Álvarez I, Urseza III Sector I, Carmen Bautista, Virgen del Cisne I, Virgen del Cisne II obtained values above the permissible color limits of 17 – 16 – 17 – 17 – 17 (PCU) respectively, for the case of arsenic, 3 samples were sent to the UPN of Quito, where the results 0.0256 – 0.0218 – 0.0213 (mg / L), are above the permissible values according to INEN 1108: 2020-04, the dissolved oxygen in all neighborhoods the results are below the permissible limits according to TULSMA BOOK VI ANNEX 1, the results of the microbiological analysis the presence of fecal coliforms was observed in 4 neighborhoods such as Harry Álvarez I, Puerto Azul, Urseza III Sector I and Portal de los Esteros Urbanization which indicates that they do not comply with the permissible limit according to INEN 1108:2020-04.
El incremento de contaminantes de origen natural o antropogénicas ha generado un deterioro en la calidad de las aguas subterráneas transformando a este recurso hídrico en una fuente no apta para el consumo humano. La protección y correcta captación de las aguas permite de esta manera garantizar la calidad de la fuente de suministro para el servicio de agua potable. Este trabajo tiene como objetivo Determinar la calidad del agua de los barrios del sector de la curva de la parroquia Puerto Bolívar que distribuye la planta de potabilización del pozo Gonzáles Rubio mediante el análisis de los parámetros físico-químicos y microbiológicos, para evaluarlos bajo la normativa nacional e internacional. Las tomas de muestras se las realizó en cada barrio en la llave de paso de la red de distribución de agua de la planta de tratamiento dentro de un periodo prudencial de 15 días; 7, 22 de noviembre y 7 de diciembre del 2021 dónde se determinaron indicadores fisicoquímicos in situ como el pH, sólidos totales disueltos, conductividad eléctrica, y temperatura mediante un analizador multiparametrico, el análisis de color, oxígeno disuelto, cloro residual y coliformes fecales fueron realizados en los laboratorios de la UTMACH, a excepción del arsénico que fue en la Universidad Politécnica Nacional de Quito. Los resultados obtenidos fueron comparados con los límites permisibles de la Norma Técnica INEN 1108:2020-04. Se demostró que la mayoría de las muestras tomadas cumplen con los indicadores fisicoquímicos a excepción de 5 barrios como el Harry Álvarez I, Urseza III Sector I, Carmen Bautista, Virgen del Cisne I, Virgen del Cisne II obtuvieron valores por encima de los límites permisibles de color de 17 – 16 – 17 – 17 - 17 (PCU) respectivamente, para el caso del arsénico se enviaron 3 muestras a la UPN de Quito, donde los resultados 0.0256 – 0.0218 – 0.0213 (mg/L), están por encima de los valores permisibles según INEN 1108:2020-04, el oxígeno disuelto en todos los barrios los resultados están por debajo de los límites permisibles según TULSMA LIBRO VI ANEXO 1, los resultados de los análisis microbiológico se observó presencia de coliformes fecales en 4 barrios como el Harry Álvarez I, Puerto Azul, Urseza III Sector I y Urbanización Portal de los Esteros el cual indica que no cumplen con el límite permisible según INEN 1108:2020-04.
Keywords: CALIDAD DEL AGUA; AGUA DE POZO; ARSENICO; COLIFORMES